Analysis of RANK-c interaction partners identifies TRAF3 as a critical regulator of breast cancer aggressiveness - Sirinian, Chaido; Papanastasiou, Anastasios D.; Karayel Eren, Özge; Degn, Soren E.; Peroukidis, Stavros; Chaniotis, Dimitrios; Nonni, Afrodite; Repanti, Maria; Kriegsmann, Mark; Makatsoris, Thomas; Koutras, Angelos; Mann, Matthias; et al. (Neoplasia, 2022)
Breast cancer is a highly heterogeneous disease both at the histological and molecular levels. We have previously shown that RANK-c is a regulator of NF-κB signaling and exerts a suppressive effect on aggressive properties of ER negative breast cancer cells, while there is an opposite effect on ER positive cell lines. In order to identify molecular determinants that govern the opposing function of RANK-c in breast cancer cells we employed the two cell lines with the highest degree of phenotypic divergence upon RANK-c-expression (SKBR3 and BT474) and identified proteins that interact with RANK-c by affinity-enrichment mass spectrometry (AE-MS) analysis. Annotating enriched proteins with NF-κB signaling pathway revealed TRAF3 as an interacting partner of RANK-c in SKBR3 cell protein lysates, but not in BT474 breast cancer cells in which RANK-c induces cell aggressiveness. To determine the role of TRAF3 in the phenotype of BT474-RANK-c cells, we reconstructed the TRAF3/RANK-c interaction both in parental BT474 and RANK-c expressing cells and tested for aggressive properties through colony formation, migration and invasion assays. TRAF3 forced expression was able to reverse BT474 phenotypic changes imposed by RANK-c, rendering cells less aggressive. Finally, TRAF3 gene expression data and TRAF3 immunohistochemical (IHC) analysis on breast cancer samples indicated that TRAF3 expression correlates with Overall Survival (OS), Recurrence Free Survival (RFS) and several clinicopathological parameters (histological grade, proliferation index) of breast cancer disease.